ANALISIS PENGARUH EKUITAS MEREK DAN KUALITAS PRODUK TERHADAP PEMBUATAN KEPUTUSAN PEMBELIAN MELALUI KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Mahasiswa FEB Universitas Diponegoro Semarang yang Pernah Memakai Produk Apple lebih Dari 1 Tahun) - Dyah Pramesti, Ardea Ayu; Hidayati, Retno (Diponegoro Journal of Management, 2023)
ABSTRACT One of the important factors in doing marketing is to build brand equity, product quality and consumer trust to produce purchasing decisions. Apple is a technology company that has successfully led the competition by holding the title of The World's Most Valuable Brands based on Forbes in 2019 and is also ranked in the top three technology brands with the most distribution of smartphones based on Canalys Smartphone Market Pulse 2019. Seeing these conditions, this study aims to analyze brand equity and product quality on purchasing decision making through consumer trust as an intervening variable for FEB Undip Semarang students. The population used in this study were FEB Undip Semarang students who had already purchased apple products. The number of samples used in this study were 150 respondents. The method of data collection is done by questionnaire. The data that has been collected is processed and analyzed using the Structural Equation Modeling (SEM) analysis technique with the AMOS 26.0 analysis tool. The results of this study indicate that consumer confidence has a positive effect on purchasing decision making. Brand Equity has a positive effect on Purchase Decision Making. Brand Equity has a positive effect on Consumer Confidence. Product quality has a positive effect on Purchase Decision Making. Product quality has a positive effect on consumer confidence